2015
DOI: 10.3747/pdi.2014.00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fluid Overload on Clinical Outcome in Southern Chinese Patients Undergoing Continuous Ambulatory Peritoneal Dialysis

Abstract: Fluid overload defined by BIA was an independent predictor for all-cause mortality and technique failure in CAPD patients. Continuous ambulatory peritoneal dialysis patients with fluid overload had a higher peritonitis rate, cardiovascular event rate, and poorer clinical outcome than those patients with normal hydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 37 publications
9
71
1
4
Order By: Relevance
“…The characteristics of patients in the 8 included studies [4,14,[33][34][35][36][37][38], which consisted of a total of 1,989 PD patients, are listed in Table 1. There were 4 studies conducted in Asia (2 in China [14,38], and 2 in Korea [33,34]), 3 studies in Europe (2 in the United Kingdom [4,36], and 1 in Switzerland [35]), and 1 study in the United States [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of patients in the 8 included studies [4,14,[33][34][35][36][37][38], which consisted of a total of 1,989 PD patients, are listed in Table 1. There were 4 studies conducted in Asia (2 in China [14,38], and 2 in Korea [33,34]), 3 studies in Europe (2 in the United Kingdom [4,36], and 1 in Switzerland [35]), and 1 study in the United States [37].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 4 studies conducted in Asia (2 in China [14,38], and 2 in Korea [33,34]), 3 studies in Europe (2 in the United Kingdom [4,36], and 1 in Switzerland [35]), and 1 study in the United States [37]. The number of patients varied from 53 [37] to 631 [34], and the mean follow-up time ranged from 1.0 year [34] to 7.5 years [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest mortality risk was in those with fluid overload and systolic BP < 130 mmHg at baseline (HR 1.51, 1.38-1.65, p < 0.001) and at 1 year (HR 1.94, 1.68-2.23, p < 0.001) [119]. Fluid overload also independently predicted all-cause mortality (HR 12.98, 1.06-168.23, p = 0.042) and a trend of increased CVD mortality (log-rank test 2.90, p = 0.089) in a trial of 307 PD patients [120]. Interestingly, a multi-centre RCT of 308 patients found that bio-impedance did not appear to improve clinical management of fluid status in PD patients [121].…”
Section: Chronic Volume Overloadmentioning
confidence: 93%
“…Measured glomerular filtration rate (mGFR) was calculated from 24-h urine collections and indexed for the body surface area. CVD was defined as a history of myocardial infarction, angina, congestive heart failure, cerebrovascular event, and peripheral vascular disease [14]. The comorbidity score was determined according to the Charlson Comorbidity Index [15].…”
Section: Data Collectionmentioning
confidence: 99%